Technical guide for wildfire impact assessments for the OEHS Professional - Medina, Enrique (Safety consultant) (American Industrial Hygiene Association (AIHA), 2018)
Wildfire impact assessments are complex by nature and can involve the investigator, property owner, laboratory, and insurance company adjuster. The OEHS professional conducting a wildfire impact investigation must define its purpose and objectives and develop a working hypothesis to drive all phases of the assessment from initial inspection, to sampling, analysis, and data interpretation. Properly documenting the extent and impact helps to evaluate a range of reasonable options for restoration to return the structure and the indoor environment as close as possible to its pre-wildfire condition, while also protecting the health and safety of restoration workers and returning occupants. This guide will assist OEHS professionals in conducting defensible wildfire impact assessments, and to evaluate restoration options to promote a safe and healthy indoor environment.